2010
DOI: 10.21859/isv.4.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an Expression Vector Containing a Novel Fusion Sequence from Middle Region of NS3 and Truncated Core Genes of Hepatitis C Virus

Abstract: Background and Aims: DNA constructs containing HCV antigens have become one of the vaccine candidates for induction of anti-HCV cellular and humoral immunity. In this study, we constructed a novel expressing vector harboring a fusion sequence derived from an overlapping fragment in the middle of NS3 and a truncated core fragment to avoid troubles reported to be associated with full gene expression. Methods: The partial NS3 (pNS3) and core genes were amplified by RT-PCR method using serum of HCV infected patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…However, the NS3 gene from the Iranian patient had more differences in gene sequence, albeit a high homology in amino acid sequence (unpublished data) in comparison to other reference sequences. Evaluation of the amplified NS3 sequence by phylogenetic analysis strongly confirmed that it belonged to 1a genotype as was previously described in detail ( 30 ).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…However, the NS3 gene from the Iranian patient had more differences in gene sequence, albeit a high homology in amino acid sequence (unpublished data) in comparison to other reference sequences. Evaluation of the amplified NS3 sequence by phylogenetic analysis strongly confirmed that it belonged to 1a genotype as was previously described in detail ( 30 ).…”
Section: Resultssupporting
confidence: 75%
“…Amplification of new partial core (aa 50-160), new overlapping region of NS3 gene covering protease/helicase domains and a fusion of both truncated fragments from HCV genotype 1a were previously described ( 30 , 31 ). In brief, full core and partial NS3 sequences were propagated from the serum of a HCV patient by RT-PCR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three adenoviral constructs expressing the middle region of the core gene and consisting of some parts of D1 and D2 (aa 50-160) and the middle region of NS3 consisting of protease and helicase (aa 1095-1387) have been developed by Hosseini et al . [15,16]. In order to retain the conformational structure and more immune response of the recombinant core, the full-length of core D1 (aa 1-118) with a flexible linker (AAY) and proteasome cleavable site and also the middle region of NS3 in fused form (rC/N) were produced without C-terminal domains of core, and without N and C-terminal sequences of NS3.…”
Section: Introductionmentioning
confidence: 99%